PRESENTATION OF A FLUXOGRAMA WITH A PROPOSE OF PREVENTIVE STRATEGY TO THE OCCURRING OF INJURIES BY REPETITIVE EFFORTS/ BONE MUSCULAR DISTURB RELATED TO THE JOB ( LER/DORT). (Fiep Bulletin - online, 2015)
Although ntaking attention due to the bad consequences that causes to several industrial and company fields, workers, Social Security, insurance agencies, Internal Comitee of Accident prevention (CIPAs), Regional Work Sation (DRT), and work unions, the LER/DORT  still keep happening in a large number at brasilian job places. Because of that, its end is still a challenge. Studies are frequently done and several solutions are presented but unfortunatelly there are few companies  that invest at the worker health or that are successful with the elaboration and practice of their prevention programs.  Believing its necessary to have the involvemnet and the comittion as basic principles, both of the companies and the empoyees, and that the grounding of this involvement is the information, this study finds its main objective: presenting a preventive propose of an easy application at the companies, and takes more than anything, simple and straight information.Taht causes both at the employee and at the employer the interest and desire of preventing. Like that, is also hoped that it can contribute so that the professionals that dedicate themselves to prevent the occupational illnes here mentioned can use them in their preventive programs, with one more triumph to ge the success of it. The fluxograma to be presented as a strategy of prevention, guides the company and the workers about ways to be gone round face to the occurring of the symptoms of LER/DORT and the allert to follow the most successful way. As the theoretical fundamentation, it used the study and opinion of some authors such as Silva (2004), Assunção (1995), Miranda e Dias (2003), Settimi (2000) and more. The methodology used was the bibliographic research and documental analysis.
Keywords: LER/DORT; FLUXOGRAMA; STRATEGY OF PREVENTION